The effect of exchange rate volatility on the nexus of technology sophistication and trade fragmentation of ASEAN5 exports to China - Hooy, Chee Wooi; Baharumshah, Ahmad Zubaidi; Brooks, Robert D. (Taylor & Francis, 2016)
This article investigates the effect of exchange rate volatility on the exports of ASEAN countries to China. Using 5-digit COMTRADE data over 1994 to 2008, the authors analyze total exports by usage, total exports by technology, and disaggregated exports of component goods by technology. Two findings are documented. First, exchange rate volatility has a negative and significant effect only on high-tech and medium-tech exports, but the magnitude implies that technology sophistication leads to higher currency volatility exposure. Second, exchange rate volatility also has a significant negative effect on parts and components exports but the elasticity is much smaller relative to the aggregate exports.